Simultaneous Laparoscopic Cholecystectomy and Endovascular Infrarenal Aortic Aneurysm Repair - Illuminati, Giulio; Calio', Francesco G.; Pasqua, Rocco; Nardi, Priscilla; Fratini, Chiara; Urciuoli, Paolo (Frontiers in Surgery, 2021)
Background/aim: The increasing indication to treat abdominal aortic aneurysms (AAA) with endovascular aneurysm repair (EVAR) and the availability of laparoscopic cholecystectomy (LC) the strategy of elective treatment of these two conditions, when associated, is not well defined. The purpose of this study was to evaluate the results of elective, simultaneous EVAR and LC. Methods: Thirteeen patients of a mean age of 72 years, with a concomitant large, asymptomatic AAA and an asymptomatic cholelithiasis underwent simultaneous EVAR and LC. Results: Postoperative mortality was absent and morbidity was 7%. The mean, total length of the procedure was 142 minutes. The mean duration of fluoroscopy was 19 minutes and the mean radiation dose was 65 mGy. The mean amount of iodinated contrast injected was 49 ml. The timing of oral fluid intake was 28 hours (range, 24 – 48 hours) and that of oral low-fat diet was 53 hours (range, 48 – 72 hours). No patient presented an infection of the aortic graft during the whole length of follow-up (mean length 41 months).The mean length of postoperative stay in the hospital was 6 days (range, 5 – 8 days). Late survival was 85% and exclusion of AAA 100%. Conclusion: Simultaneous EVAR and LC can be performed safely, allowing effective and durable treatment of both conditions.